2017
DOI: 10.1182/bloodadvances.2017009019
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of FLT3-TKD and NPM1 mutations defines a highly favorable prognostic AML group

Abstract: Key Points• FLT3-TKD/NPM1 double mutation status is associated with superior relapse-free survival compared with NPM1-only-mutated AML.• Allogeneic stem cell transplant in complete responders does not improve outcomes in FLT3-TKD/NPM1 AML patients. and a trend toward improved overall survival (OS).The presence of FLT3-TKD/NPM1 double mutation status was an independent positive predictor in multivariable analysis. Allogeneic stem cell transplant did not improve outcomes in the FLT3-TKD/NPM1 cohort. Consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…Interestingly, the co-occurrence of NPM1 and FLT3 mutations is consolidated [112], with a frequency near to twice that of correlation with the wild-type form, suggesting a direct molecular link between them, which has not yet been investigated. This combination is associated with an intermediate prognosis [116]. Moreover, DNMT3A, IDH1, IDH2 and TET2 mutations are identified as concomitant to NPM1 mutations [12,117], confirming the dynamic interplay among AML tumor suppressors.…”
Section: Npm1 Mutationsmentioning
confidence: 75%
“…Interestingly, the co-occurrence of NPM1 and FLT3 mutations is consolidated [112], with a frequency near to twice that of correlation with the wild-type form, suggesting a direct molecular link between them, which has not yet been investigated. This combination is associated with an intermediate prognosis [116]. Moreover, DNMT3A, IDH1, IDH2 and TET2 mutations are identified as concomitant to NPM1 mutations [12,117], confirming the dynamic interplay among AML tumor suppressors.…”
Section: Npm1 Mutationsmentioning
confidence: 75%
“…Allogeneic stem cell transplantation in first complete remission (CR1) was associated with a reduced relapse risk in all molecular subgroups with the exception of NPM1mut AML with absent or low ratio FLT3-ITD [27]. Another study showed patients with co-mutated NPM1 and FLT3-TKD may have an exceptionally favorable prognosis [28]. ELN-2017 guidelines recommend upfront testing for FLT3 and measurement of allele ratio (AR) for the prognosis risk stratification.…”
Section: Flt3mentioning
confidence: 99%
“…Furthermore, FLT3-TKD 1 NPM1c 1 AML patient blasts showed a reduction in FLT3 surface levels as well as increased ER localization of FLT3 compared with FLT3-TKD 1 NPM1 wt blasts ( Figure 2K; supplemental Figure 7B-C). Interestingly, recent human studies suggest that presence of NPM1c significantly changes the prognosis of FLT3-TKD-positive patients, 18 thereby emphasizing the need for elucidating mechanistic links between FLT3-TKD and NPM1c in molecular and murine model studies.…”
Section: Presence Of Npm1c Shifts Flt3-d835y Localization To the Endomentioning
confidence: 99%